How do perceptions of other customers affect satisfaction and loyalty in public aquatic centres?. Issue 6 (2nd November 2017) - Afthinos, Yanni; Theodorakis, Nicholas D.; Howat, Gary
ABSTRACT: The aim of the present study was to examine the impact of perceptions of other customers on overall satisfaction and loyalty in the context of public aquatic centres. The proposed relationships were examined using empirical data from 299 customers of four Greek aquatic centres. Structural equation modelling analysis revealed that (a) the Other Customer Perception (OCP) scale [Brocato, E. D., Voorhees, C. M., & Baker, J. (2012). Understanding the influence of cues from other customers in the service experience: A scale development and validation. Journal of Retailing, 88 (3), 384–398] has strong psychometric properties indicating evidence of convergent validity, discriminant validity, and construct reliability, and (b) two of the three OCP dimensions, similarity and suitable behaviour, significantly predicted satisfaction and loyalty for aquatic centre customers. In contrast, the third OCP dimension, physical appearance, did not significantly influence satisfaction or loyalty. Finally, results showed that satisfaction has an impact on loyalty. Practical implications for aquatic centres managers are discussed.